Ambiguity and investor behavior - Dimitrios Kostopoulos; Steffen Meyer; Charline Uhr (Leibniz Institute for Financial Research SAFE, 2020)
We relate time-varying aggregate ambiguity (V-VSTOXX) to individual investor trading. We use the trading records of more than 100,000 individual investors from a large German online brokerage from March 2010 to December 2015. We find that an increase in ambiguity is associated with increased investor activity. It also leads to a reduction in risk-taking which does not reverse over the following days. When ambiguity is high, the effect of sentiment looms larger. Survey evidence reveals that ambiguity averse investors are more prone to ambiguity shocks. Our results are robust to alternative survey-, newspaper- or market-based ambiguity measures.
Keywords: D10; D81; D90; G11; G40; 330; ambiguity; uncertainty; individual investor; risk-taking; trading behavior